Sensitivity pattern of streptococcus pneumoniae among pre-school childhood carriers - Malik, Alam Sher; Ismail, Asma
Streptococcus pneumoniae (S.pneuinoniae) is the most common bacterial cause of pneumonia, meningitis and otitis media, with the highest incidence among young children and the elderly. S.pneumoniae was once considered to be routinely susceptible to penicillin, but since the mid-1980s the incidence of resistance to penicillin and other microbiological agents had been increasing. Resistant strains have been reported from all over the world. To optimise the empirical regimens and initial therapy for pneumococcal infections, clinical health-care providers must be informed about the prevalence and pattern of drug resistance among the isolates in their communities. No such data is available for the Malaysian population. The aim of this study was to determine the sensitivity pattern of S.pneumoniae in carriers among pre-school children. Nasopharyngeal and oropharyngeal swabs were collected from children of 1 month to 6 years of age. S.pneumoniae organisms were identified according to the standard procedures. All isolates were tested for penicillin resistance with a 1 oxacillin disk by the Kirby-Bauer disk diffusion methods. A total of 502 (nasopharynx 355, oropharynx 147) specimens were obtained from kindergarten students, inpatients and paediatric clinics over a period of one year. Thirty seven carriers were detected: 36 from nasopharynx and 1 from oropharynx swabs. The children with age between 4 to 6 years, had the highest carriage rate (10.43%). The carriage rate was higher in children who: (1) were institutionalised (2) have 2-4 siblings (3) are malnourished ( 4) live in urban area. All isolates, except one, were sensitive to penicillin. The resistant isolate was sensitive to cephalosporin group of antibiotics. Overall about 10% of the pre-school children were carriers. S.pneumoniae was isolated significantly more often (p<O.OOl) from the nasopharynx than from the oropharynx and 2.7% of the organosms in carrier children were resistant to penicillin.In conclusion in Kota Bharu use of penicillin as an empirical and initial therapy for pneumococcal infection can be· continued, however a close monitoring for the sensitivity of this organism is recommended.